Clinical applications of liquid biopsies for early lung cancer detection - Zheng, Hao (Am J Cancer Res, 2019)
Over the past decade, the clinical utility of liquid biopsies in lung cancer has drawn increasing attention. Having been successfully applied in targeted therapy for late stage lung cancer, liquid biopsies are being further investigated regarding their potential role for early detection of lung cancer. Novel biomarkers with high sensitivity and specificity are crucial for identifying patients at early stages as well as for monitoring high-risk populations. A variety of bodily fluids (such as plasma, serum, and sputum) and biomarkers (such as cfDNA, CTCs, gene methylation, and miRNA) have been investigated for their potential role in the diagnosis of lung cancer. In this review, we summarize recent advances in circulating biomarkers regarding the early detection of lung cancer and discuss their potential applications and challenges in clinical settings.